2021
DOI: 10.1007/s10725-021-00694-9
|View full text |Cite
|
Sign up to set email alerts
|

Generation of new salt-tolerant wheat lines and transcriptomic exploration of the responsive genes to ethylene and salt stress

Abstract: Background: Wheat (Triticum aestivum L.) is a staple crop in the world, but is only moderately salt tolerant. However, salt stress affects one-fth of irrigated agricultural land in the world, it is of great importance to cultivate salt-tolerant varieties to improve the global wheat production.Results: In this study, over 90,000 wheat seeds of cultivar 'Luyuan502' were mutated by EMS, and 2000 salt-tolerant lines were harvested from salinized eld. By analysis of ethylene sensitivity, salt related physiological … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…As a result, the light-harvesting complex proteins were stabilized in the well-organized chloroplast that improved the photosynthesis under salt stress. Ma et al 62 found that wheat mutant lines with decreased ethylene sensitivity exhibited enhanced salt tolerance, suggesting ethylene sensitivity relation to salt tolerance. Overexpression of TaERF3 (an ethylene-response factor) in wheat resulted in increased tolerance to salt and drought stress 63 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the light-harvesting complex proteins were stabilized in the well-organized chloroplast that improved the photosynthesis under salt stress. Ma et al 62 found that wheat mutant lines with decreased ethylene sensitivity exhibited enhanced salt tolerance, suggesting ethylene sensitivity relation to salt tolerance. Overexpression of TaERF3 (an ethylene-response factor) in wheat resulted in increased tolerance to salt and drought stress 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant hormones play important roles in various stress responses. For instance, ABA is thought to be essential for plant responses to abiotic stresses in many plant species including wheat, rice, and Magnolia wufengensis [19,25,37]. For example, it was reported that the rice Osnced5 mutant reduced the ABA level and decreased salt tolerance, while OsNCED5 overexpression increased the ABA level and enhanced salt tolerance, indicating the importance of ABA to the salt tolerance of rice [37].…”
Section: Plant Hormones Play Regulatory Roles In Quinoa Responses To Ethylene and Salt Stressmentioning
confidence: 99%
“…Ethylene also functions in plant responses to salt stress. For example, the Arabidopsis ethylene insensitive mutants ethylene response1-1 (etr1-1), etr2-1, ethylene insensitive2-1 (ein2-1), ein2-5, ein3-1, and ein4-1 showed reduced salt tolerance [22][23][24], while the tobacco and wheat mutants with reduced ethylene sensitivity exhibited increased salt resistance [25,26]. It was reported that ethylene was important for salt responses of Arabidopsis, grapevines, maize, and tomato, and ethyleneregulated salt responses in plants mainly by maintaining the homeostasis of Na + /K + ratio, nutrients, and ROS, and the assimilation of nitrates and sulfates [27].…”
Section: Introductionmentioning
confidence: 99%
“…The cyanoamino acid metabolism is important for resistance to abiotic stresses such as drought (Li et al 2017) and salt (Ma et al 2021b). In this metabolic process, cyanogenic glycosides, including dhurrin, linamarin, and lotaustralin, are the products; these products can be converted back to the reactants, which are catalyzed by beta‐glucosidase (Figure 9C).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noticed that, during phenylalanine metabolic process, besides lignin, other biologically important compounds such as flavonoids (anthocyanins), stilbenes and gingerol catalyzed by 4-coumarate-CoA ligase 3 are also produced (Figure 9A). These compounds play an The cyanoamino acid metabolism is important for resistance to abiotic stresses such as drought (Li et al 2017) and salt (Ma et al 2021b). In this metabolic process, cyanogenic glycosides, including dhurrin, linamarin, and lotaustralin, are the products; these products can be converted back to the reactants, which are catalyzed by beta-glucosidase (Figure 9C).…”
Section: Differentially Enriched Pathways Were Induced By Pi Starvati...mentioning
confidence: 99%